2018
DOI: 10.1016/j.triboint.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear characteristics of TiO 2 nano-additive water-based lubricant on ferritic stainless steel

Abstract: Friction and wear characteristics of TiO2 nano-additive water-based lubricant on Friction and wear characteristics of TiO2 nano-additive water-based lubricant on ferritic stainless steel ferritic stainless steel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 69 publications
1
64
0
Order By: Relevance
“…The reason may explain as follows: Firstly, the long alkyl chains absorb on the stainless steel surface and form physical boundary lubrication film. Secondly, during the friction under high pressure, the active phosphorus in the RSOPE can react with metal and generate tribochemical reaction film [23][24][25]. Fig.…”
Section: Antiwear and Friction-reducing Performancementioning
confidence: 99%
“…The reason may explain as follows: Firstly, the long alkyl chains absorb on the stainless steel surface and form physical boundary lubrication film. Secondly, during the friction under high pressure, the active phosphorus in the RSOPE can react with metal and generate tribochemical reaction film [23][24][25]. Fig.…”
Section: Antiwear and Friction-reducing Performancementioning
confidence: 99%
“…Therefore, when the concentration of nano-TiO 2 is lower than 4.0 wt%, there are insufficient TiO 2 NPs left to form lubricating film and make rolling effect due to loss of nanolubricants when contacting the hot steel surface. When the concentration of nano-TiO 2 exceeds 4.0 wt% to a higher level of 8.0 wt%, instead, the rolling force varies at an opposite trend to present a higher value (see Figure 2) because of the agglomeration of TiO 2 NPs [20,21], which aggravates the friction between the work roll and the workpiece.…”
Section: Fib-tem Analysismentioning
confidence: 99%
“…In this regard, a type of environment-friendly lubricant with excellent lubricating performance is urgently needed to substitute conventional oil-containing lubricants. In recent years, the research trend on water-based lubricants added with nanoparticles (NPs) is continuously ascending due to their excellent tribological properties and promising potential in hot steel rolling, even though the relevant reports are still scarce [8,[16][17][18][19][20][21][22][23]. For instance, Bao et al [8] carried out hot steel rolling tests at temperatures of 750-950 • C using water-based lubricants containing SiO 2 NPs, and found that the use of as-prepared lubricants with the addition of 0.5 wt% nano-SiO 2 resulted in improved surface morphology, reduced oxide scale thickness, and refined grain size, compared to that of the base lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…Steel/steel and steel/copper friction pairs are typical moving parts in machines such as bearings and hydraulic pumps. Several studies have been conducted on friction and wear in steel/copper [1][2][3][4][5][6] and steel/steel [7,8] friction pairs under lubricated or dry friction conditions. In general, steel has relatively low wear during friction owing to its high hardness according to the Archard wear equation [9].…”
Section: Introductionmentioning
confidence: 99%